(3MGQS GdeQei aj cQI GdjOs - (3OQhjT ceGds; (3YeGO GdOjf YHGS GHhRjO s ((3GdbGgQIs (3eQcR GdcJGH ddfTQs, 1998)
(3d Y (B681 (3GMJhi Ydi HYV GdegGQGJ GdafjI GdCSGSjI GdeSJNOeI aj GdHWhdGJ GdYGdejI h GdNGUI HcQI GdbOe ,MjK bOe UaGJ GddGYH GdegGLe h GdbjGSGJ GdafjI dGNJHGQ GddGYH GdcaA ,eOYe HHQfGeL JOQjHj h NWI aQjb(B.s
Keywords: (3cQI GdjOs